A systematic review of the relationship between severe maternal morbidity and post-traumatic stress disorder - Furuta Marie; Sandall Jane; Bick Debra (BMC, 2012)
Abstract Background The incidence of severe maternal morbidity is increasing in high-income countries as a consequence, in part, of increased obstetric intervention and increasingly complex medical needs of women who become pregnant. Access to emergency obstetric care means that for the majority of women in these countries, an experience of severe maternal morbidity is unlikely to result in loss of life. However, little is known about the subsequent impact on postnatal psychological health resulting in an evidence gap to support provision of appropriate care for these women. There has recently been increasing recognition that childbirth can be a cause of post-traumatic stress disorder (PTSD). The combination of experiencing a life-threatening complication and its management may culminate in psychological trauma. This systematic review examined the association between women's experience of severe maternal morbidity during labour, at the time of giving birth or within the first week following birth, and PTSD and its symptoms. Methods Relevant literature was identified through multiple databases, including MEDLINE, PsycINFO, EMBASE, CINAHL, British Nursing Index, Web of Science, Cochrane library and the British Library, using predetermined search strategies. The search terms included "post-traumatic stress disorder", "PTSD", "stress disorders, post-traumatic", "maternal morbidity", "pregnancy complications" "puerperal disorders", "obstetric labo(u)r complication", "postpartum h(a)emorrhage", "eclampsia". Studies identified were categorised according to pre-defined inclusion and exclusion criteria. The quality of included studies was assessed using the relevant CASP appraisal tools. Results Eleven primary studies met review criteria. Evidence of a relationship between severe maternal morbidity and PTSD/PTSD symptoms was inconsistent and findings varied between studies. Nevertheless, there is some evidence that severe pre-eclampsia is a risk factor for PTSD and its symptoms, an association possibly mediated by other factors such as fetal/neonatal condition. Conclusions Despite the absence of robust evidence regarding the relationship between severe maternal morbidity and PTSD/PTSD symptoms, it is crucially important that clinicians and policy makers are aware of a potential higher risk of PTSD among women who experience severe morbidity. Further studies are now needed to confirm this risk as well as to understand underlying mechanisms in order to minimise the longer term psychiatric impact of severe maternal morbidity.